Advances in Pacific Basin business, economics and finance - Lee, Cheng F.; Yu, Min-teh (Bingley, UK : Emerald Publishing Limited, 2018)
Advances in Pacific Basin Business, Economics, and Finance is an annual publication designed to focus on interdisciplinary research in finance, economics, and management among Pacific Rim countries.
The Choice of Industrial Diversification Strategy for Public Listed Firms in the Hotel IndustryAbstract; 1. Introduction; 2. Literature Review; 3. Data and Methodology; 4. Results and Discussion; 4.1. Descriptive Statistics; 4.2. Regression Results and Discussion; 4.2.1. The Influence of Related and Unrelated Diversification Entropy Index on Firm Performance; 4.3. Nonlinear Relationship between Degree of Diversification and Firm Performance; 4.3.1. The Influence of Crisis on the Relationship between Diversification and Firm Performance; 4.4. Robustness Test
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 17, 2018).
Master record variable field(s) change: 050, 082
Keywords: Pacific Area -- Economic conditions; Finance -- Pacific Area; Pacific Area -- Commerce; Pacific Area -- Foreign economic relations; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; Commerce; Economic history; Finance; International economic relations; Pacific Area; Electronic books